Factors Affecting Interest in Revisiting Kare Tourism Village Based on Structural Equation Modeling - M Fariz Fadillah Mardianto; Elly Pusporani; Suliyanto Suliyanto; Sri Endah Nurhidayati; Na’imatul Lu’lu’a; Marcelena Vicky Galena (Inferensi, 2026)
This research focuses on analyzing the factors that affect tourists' intentions to revisit Kare Tourism Village. Utilizing quantitative methods, primary data were gathered through questionnaires from 105 tourists who had previously visited the village. The SEM-PLS method was employed for analysis. In this study, several latent variables were identified, including facilities and services in Kare Tourism Village as exogenous latent variables, tourist satisfaction as both an endogenous latent variable and an intermediate variable, and tourist interest as the dependent variable. The findings reveal an value of 0.876 for tourist satisfaction, indicating that 87.6% of the variation in satisfaction can be explained by the model, which is considered strong. In contrast, the R² value for tourist interest is 0.548, suggesting that 54.8% of the variation in interest is explained by the model, classified as moderate. Additionally, the GoF value of 0.673 demonstrates a high model fit. Furthermore, the service variables in Kare Tourism Village significantly impact tourist satisfaction.